Demographic and genetic collapses in spatially structured populations: insights from a long‐term survey in wild fish metapopulations. Issue 2 (24th September 2018) - Mathieu‐Bégné, Eglantine; Loot, Géraldine; Chevalier, Mathieu; Paz‐Vinas, Ivan; Blanchet, Simon
Abstract : Unraveling the relationship between demographic declines and genetic changes over time is of critical importance to predict the persistence of at‐risk populations and to propose efficient conservation plans. This is particularly relevant in spatially structured populations (i.e. metapopulations) in which the spatial arrangement of local populations can modulate both demographic and genetic changes. We used ten‐year demo‐genetic monitoring to test 1) whether demographic declines were associated with genetic diversity declines and 2) whether the spatial structure of a metapopulation can weaken or reinforce these demographic and genetic temporal trends. We continuously surveyed, over time and across their entire range, two metapopulations of an endemic freshwater fish species Leuciscus burdigalensis : one metapopulation that had experienced a recent demographic decline and a second metapopulation that was stable over time. In the declining metapopulation, the number of alleles rapidly decreased, the inbreeding coefficient increased, and a genetic bottleneck emerged over time. In contrast, genetic indices were constant over time in the stable metapopulation. We further show that, in the declining metapopulation, demographic and genetic declines were not homogeneously distributed across the metapopulation. We notably identify one local population situated downstream as a 'reservoir' of individuals and genetic variability that dampens both the demographic and genetic declines measured at the metapopulation level. We demonstrate the usefulness of long‐term monitoring that combines both genetic and demographic parameters to understand and predict temporal population fluctuations of at‐risk species living in a metapopulation context.